Towards banking jurisprudence: Understanding Islamic banking products in Malaysia - Mohd Yunus, Saidatolakma; Kamaruddin, Zuraidah; Embong, Rahimah (International Journal of Academic Research in Business and Social Sciences, 2017)
Since product of Islamic banking is among the factors that are able to create customers’ satisfaction to the system, it is extremely important to bring understanding to the customers on the products. Good understanding the customers have and good quality products the banks offer will bring success to the bank. However, with the emergence of so many banking institutions introducing the Islamic banking products and services, the amount of the products are not well in knowledge, different terminologies and principles in Sharia used by different banking institutions lead to confusion within the customers. Thus this study is trying to analyze the Islamic banking products offered and the mechanisms employed by all Islamic banks in Malaysia. It is believed that by highlighting the products and the mechanisms applied, customers’ perception and attitude towards Islamic banking products will change from negative to positive and it is also believed that, it will bring adequate knowledge to the customers in understanding Islamic banking products and give trust to them when dealing with Islamic banks in Malaysia.